Colonisation of soft lining materials by micro-organisms - Pavan, Sabrina [UNESP]; Santos, Paulo Henrique dos [UNESP]; Arioli Filho, João Neudenir [UNESP]; Palomare Spolidorio, Denise Madalena [UNESP] (Wiley-Blackwell, 2010)
Objective:This study evaluated the in vitro adherence of pathogenic micro-organisms, Candida albicans, Staphylococcus aureus and Pseudomonas aeruginosa, to soft lining materials and their inhibitory effect on these micro-organisms.Materials and Methods:To measure adherence, specimens of Molloplast B and Ufi Gel P were inoculated [107 colony-forming units per millimetre (cfu/ml)] with TSB media containing the micro-organisms. To determine the number of micro-organisms in the 10-2-10-5 dilutions, 25 mu l of the suspension were transferred to plates of selective media. Colony counts of each specimen were quantified (cfu/ml). The surface roughness was measured with a perfilometer to assess the relationship between the adherence of micro-organisms and surface roughness of each material. For the inhibition test, specimens of materials were placed in agar plates inoculated individually with the micro-organisms. After 48 h, the inhibition zones around the specimens were measured.Results:None of the materials exhibited inhibition zones. The number of cfu/ml of S. aureus and P. aeruginosa were significantly greater than C. albicans for both materials. The Ufi Gel P exhibited greater adherence of C. albicans than Molloplast B. No correlation was observed between the adherence of micro-organisms and surface roughness.Conclusion:The surface roughness of the materials is not the only factor governing micro-organism adherence.
Keywords: soft lining materials; micro-organisms; surface roughness; colonisation